Kindlin-2 induced by TGF-β signaling promotes pancreatic ductal adenocarcinoma progression through downregulation of transcriptional factor HOXB9. Issue 1 (28th May 2015) - Zhan, Jun; Song, Jiagui; Wang, Peng; Chi, Xiaochun; Wang, Yunling; Guo, Yongqing; Fang, Weigang; Zhang, Hongquan
Highlights Kindlin-2 is upregulated but HOXB9 is downregulated by TGF-β1 in PDAC cells. Kindlin-2 upregulates but HOXB9 downregulates TβRI in PDAC cells. Kindlin-2 and TGFβ signaling constitute a positive feedback loop that regulates PDAC progression. Enhanced expression of Kindlin-2 predicts a poor prognosis for PDAC patients.